2022
DOI: 10.1111/jhn.13077
|View full text |Cite
|
Sign up to set email alerts
|

Using social media analysis to study population dietary behaviours: A scoping review

Abstract: Background: The rapid adoption and sustained use of social media globally has provided researchers with access to unprecedented quantities of lowlatency data at minimal costs. This may be of particular interest to nutrition research because food is frequently posted about and discussed on social media platforms. This scoping review investigates the ways in which social media is being used to understand population food consumption, attitudes and behaviours. Methods: The peer-reviewed literature was searched fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
(93 reference statements)
0
4
0
Order By: Relevance
“…Social networks have been used to understand population health in some communities [17], while gamification has inspired medication adherence applications [18]. Ideas from the "Internet of Things" have led to active medication inhalers that measure and report their use [19], giving rise to ethical concerns and, as with other remote monitoring, to questions of technology acceptance [20].…”
Section: Design Personal Health Records Decision Supportmentioning
confidence: 99%
“…Social networks have been used to understand population health in some communities [17], while gamification has inspired medication adherence applications [18]. Ideas from the "Internet of Things" have led to active medication inhalers that measure and report their use [19], giving rise to ethical concerns and, as with other remote monitoring, to questions of technology acceptance [20].…”
Section: Design Personal Health Records Decision Supportmentioning
confidence: 99%
“…Social media is another area of interest as food is a frequent topic of discussion in media posts, providing an extensive qualitative data set. Titova et al 16 considered the potential of using social media for understanding population‐level patterns of food intake and dietary behaviours. They found that although there was great potential for such social media analysis as a research tool, with low costs and rapid collection of data there are inadequate methodological and ethical frameworks in place to ensure academic rigour.…”
mentioning
confidence: 99%
“…While the data can only be generalised to the population who make the posts, the data do offer insights into what people are eating and thinking about food. In a review of studies using social media to study dietary behaviours, 71 studies were identified from 2003 (inception of My Space) to 2021, with most studies published from 2016 onwards 10 . It was found that only two of the studies included a researcher qualified in nutrition.…”
mentioning
confidence: 99%
“…In a review of studies using social media to study dietary behaviours, 71 studies were identified from 2003 (inception of My Space) to 2021, with most studies published from 2016 onwards. 10 It was found that only two of the studies included a researcher qualified in nutrition. Topics varied from analyses of a small number of posts to using methods to study millions of posts.…”
mentioning
confidence: 99%